An evaluation of life cycle assessment and cost-benefit analysis of an ecoprint fabric micro, small, and medium enterprise in Yogyakarta - Lathiifah Thawafani; Bella Renata Valencia; Muhammad Achirudin Buchari; Arie Dwi Zarliansyah; Nur Mayke Eka Normasari; Sinta Rahmawidya Sulistyo; Yoshi Budiyanto (OPSI, 2026)
The rapid growth of the fashion industry has led to the emergence of fast fashion, which often overlooks its environmental impacts. In contrast, environmentally conscious practices are being adopted by some enterprises, including an MSME located in Yogyakarta, Indonesia, specializing in ecoprint fabric production. To evaluate its environmental and economic performance, this study conducts a Life Cycle Assessment (LCA) and Cost-Benefit Analysis (CBA) focusing on green production, green transportation, and green packaging. LCA results show that the use of LPG in the steaming process has notable environmental impacts, particularly in fossil depletion (0.00076), climate change–human health (0.000359), and human toxicity (0.0000956). Based on these findings, Solar PV was evaluated as an improvement condition to reduce dependence on LPG and mitigate environmental impacts across several categories. However, human toxicity increased from 9.56E-05 to 0.00164, indicating environmental trade-offs throughout the life cycle. The CBA results indicate that the existing production system is economically feasible, with NPV of IDR 58,781,312, IRR of 9%, BEP of 2,136.34 units (IDR 534,084,829.96), Payback Period of 5.52 years, and BCR of 1.40. This implies that the project is already economically feasible under current LPG use, while the substitution with Solar PV further enhances its sustainability and overall benefits.